2016
DOI: 10.4028/www.scientific.net/kem.685.417
|View full text |Cite
|
Sign up to set email alerts
|

Improving Reliability of Hot Plate Mill Electromechanical System

Abstract: The paper considers issues of a mathematical model development of a “deformation zone - main electric drive” concerning hot plate mills. The dependence of the calculation of rolling torque on features of high deformation zone is given. Based on the obtained expressions, the structural diagram of the deformation zone model has been developed. The paper specifies the structure of the mathematical model for electric drive speed control system based on the known equations of synchronous motor. After the comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Calculations were performed using data arrays recorded in the online mode. The oscillograms obtained in the study of elastic torques for individual passes confirmed the conclusion of high dynamic loads on the spindles when the workpiece enters the stand [66,67]. However, they were not statistically processed, and their impact on the spindle's technical condition was not assessed.…”
Section: Innovative Solutionsmentioning
confidence: 80%
“…Calculations were performed using data arrays recorded in the online mode. The oscillograms obtained in the study of elastic torques for individual passes confirmed the conclusion of high dynamic loads on the spindles when the workpiece enters the stand [66,67]. However, they were not statistically processed, and their impact on the spindle's technical condition was not assessed.…”
Section: Innovative Solutionsmentioning
confidence: 80%
“…The diagnosis algorithm of the FC gripping accuracy was developed on the basis of analysis carried out of methods of quality control for FC gripping in the process of bulk material packaging. The present algorithm was represented as a functional model which was made in IDEF0 notation with the help of the Ramus Educational software environment [19][20][21][22][23][24][25][26][27][28]. The diagram of first-level decomposition is presented in Figure 5.…”
Section: Development Of the Algorithm For The Machine Vision Systemmentioning
confidence: 99%
“…Непрерывные прокатные станы являются сложными многосвязными агрегатами [1][2][3][4][5][6], которые требуют обеспечения точного соответствия технологических режимов заданным параметрам [7][8][9][10][11][12][13][14]. Возможности исследования процессов на реальных объектах ограничены, поэтому широко применяют методы моделирования [15][16][17].…”
Section: Introductionunclassified